Effectiveness of Posterior Laminoforaminotomy in the Management of Lateral Cervical Soft Disc Herniation (Medical Forum Monthly, 2024)
ABSTRACTObjective: The outcome of this study will therefore determine the suitability of posterior laminoforaminotomy in the treatment of lateral cervical soft disc herniation.Study Design: observational studyPlace and Duration of Study: This study was conducted at the Department of Neurosurgery MTI HMC Peshawar from July 2022 to June 2023.Methods: A total of fifty four patients were included in this study for the surgical management of lateral cervical soft disc herniation with laminoforaminotomy. The measure of effectiveness was done using Odom’s criteria. All the analysis of the data was done employing SPSS.Results: The patients’ mean age was 42. 04±11, 57 years. The Odom’s criteria to determine the efficacy were excellent in 39 (72. 2%) patients, good 10 (18. 5%), fair 3 (5. 6%) and poor 2 (3. 7%).Conclusion: Posterior laminoforaminotomy can be recommended as an effective method of surgical treatment for lateral cervical soft disc herniation.